AI and Language in the Urban Context : Conversational Artificial Intelligence in Cities - Richard Coyne (Routledge, 2025)
In a world influenced increasingly by artificial intelligence (AI), the city emerges as a dynamic hub of digital conversations. AI and Language in the Urban Context offers a novel exploration of how AI, particularly large language models (LLMs), is transforming urban environments. Moving beyond the typical technological narratives, this book draws on the author's unique expertise in design, semiotics and hermeneutics to present a critical cultural perspective on AI's role in the city.Focusing on the intersection of urban theory and AI, the book reveals how conversational AI is reshaping social interactions, decision-making processes, and media in urban spaces. By merging practical knowledge of AI algorithms with an understanding of urban practices, the author highlights the opportunities and challenges AI presents for modern cities.This book is essential for anyone interested in the future of urban living. It provides a deep dive into the technical, social and cultural implications of AI in cities, offering practical examples and philosophical insights. Readers will gain a comprehensive understanding of how AI is influencing the design, governance and dynamics of urban life in the digital age.The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.